Comparison of the Direct Oral Anticoagulants and Warfarin in Patients With Atrial Fibrillation and Valvular Heart Disease: Updated Systematic Review and Meta-Analysis of Randomized Controlled Trials - Bitar, Yasmin de Souza Lima; Duraes, Andre Rodrigues; Roever, Leonardo; Gomes Neto, Mansueto; Lins-Kusterer, Liliane; Bocchi, Edimar Alcides (Frontiers in Cardiovascular Medicine, 2021)
Background: Direct oral anticoagulants (DOACS) are approved for use in non-valvular atrial fibrillation (AF). This systematic review and meta‐analysis aimed to evaluate the efficacy and safety of DOACs versus warfarin and update the evidence for treatment of AF and valvular heart disease (VHD). Methods: We identified randomized clinical trials (RCTs) and post-hoc analyses comparing the use of DOACS and Warfarin in AF and VHD, including biological and mechanical heart valves (MHV), updating from 2010 to 2020. Through systematic review and meta-analysis, by using the 'Rev Man' program 5.3, the primary effectiveness endpoints were stroke and systemic embolism (SE). The primary safety outcome was major bleeding, while the secondary outcome included intracranial hemorrhage. We performed prespecified subgroup analyses. Data were analyzed by risk ratio (RR) and 95% confidence interval (CI) and the I-square (I2) statistic as a quantitative measure of inconsistency. Risk of bias and methodological quality assessment of included trials was evaluated with the modified Cochrane risk‐of‐bias tool. Results: We screened 326 articles and included 8 RCTs (n = 14.902). DOACs significantly reduced the risk of stroke/SE (RR 0.80, 95% CI: 0.68-0.94; P = 0.008; moderate quality evidence; I2 = 2%) and intracranial hemorrhage (RR 0.40, 95% CI: 0.24-0.66; P = 0.0004; I2 = 49%) with a lower risk of major bleeding (RR 0.83, 95% CI: 0.56-1.24; P =0.36; I2 = 88%) compared to Warfarin. This difference was persistent in a subgroup analysis of bioprosthetic valves and AF. Conclusions: In this update, DOACs remained with similar efficacy and safety compared to warfarin in thromboprophylaxis for AF and VHD.